2003
DOI: 10.1071/ar02178
|View full text |Cite
|
Sign up to set email alerts
|

Potential of SSR markers for plant breeding and variety identification in Australian barley germplasm

Abstract: SSR markers closely linked to 18 loci that control 16 important barley traits were assessed for their applicability in Australian barley breeding programs. A panel of 40 genotypes routinely used by the South Australian Barley Improvement Program (SABIP) was used to examine the usefulness of these SSR markers for marker assisted selection (MAS). The success of monitoring a trait locus from donor to recipient lines ranged from 10 to 98%, depending on the marker. SSRs with a high polymorphic information content (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 39 publications
1
40
2
2
Order By: Relevance
“…Furthermore, many of the modern high yielding varieties and hybrids are phenotypically less distinct making morphological evaluation more diYcult. Microsatellite markers have been used for genetic characterization of cultivars in wheat, maize, sunXower and tomato (Karkousis et al 2003;Wang et al 2002;Zhang et al 2005;Smith and Register 1998). The Biochemical and Molecular Techniques Group of the International Union for the Protection of New Varieties of Plants (UPOV) is evaluating diVerent DNA marker parameters prior to its routine use in establishing distinctness, uniformity and stability (DUS) of plant varieties (Bredemeijer et al 2002;UPOV-BMT 2002).…”
Section: Use Of Informative Ssr Markers In Assessment Of Impurities Imentioning
confidence: 99%
“…Furthermore, many of the modern high yielding varieties and hybrids are phenotypically less distinct making morphological evaluation more diYcult. Microsatellite markers have been used for genetic characterization of cultivars in wheat, maize, sunXower and tomato (Karkousis et al 2003;Wang et al 2002;Zhang et al 2005;Smith and Register 1998). The Biochemical and Molecular Techniques Group of the International Union for the Protection of New Varieties of Plants (UPOV) is evaluating diVerent DNA marker parameters prior to its routine use in establishing distinctness, uniformity and stability (DUS) of plant varieties (Bredemeijer et al 2002;UPOV-BMT 2002).…”
Section: Use Of Informative Ssr Markers In Assessment Of Impurities Imentioning
confidence: 99%
“…Microsatellite primers and PCR multiplexing Twenty highly polymorphic SSR markers (Malysheva-Otto et al 2006;Hamza et al 2004;Matus and Hayes 2002;William et al 1997;Davila et al 1999;Saghai Maroof et al 1994;Karakousis et al 2003) covering the whole barley genome were used (Table 2). They included 17 genomic and 3 genic (HVCMA, HVLTPBB, HVWAXY) SSR markers.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The authors hypothesized that it was the result of linkage of these markers to major loci for disease resistance or malting quality that were presumably under selection during the breeding process. Several authors have indicated changes in allelic frequencies, with a reduction in diversity for modern cultivars (Russell et al 2000;Karakousis et al 2003). Similarly, Fu and Somers (2009) using wheat microsatellites reported that allelic reduction occurred in every part of the wheat genome as a consequence of breeding.…”
Section: Discussionmentioning
confidence: 95%
“…The considerable differences between allelic frequencies at the F2 and F8 of the same cross are, most likely, the result of artificial selection. Karakousis et al (2003), using microsatellites, found that several SSRs assessed in F2 crosses showed distorted segregation, while others showed the expected 1:2:1 ratio. They explained this result as a consequence of preferential amplification of alleles, resulting in the inability to detect heterozygote's for some markers.…”
Section: Discussionmentioning
confidence: 98%